Dissociation constant measurement using combination tapered fiber-optic biosensor (CTFOB) dip-probes - Wang, Chun-Wei (2010)
The document reports a novel method of measuring dissociation constant (k(D)) of antibody-antigen interaction using evanescent wave based combination tapered fiber-optic biosensor (CTFOB) dip-probes. The method was demonstrated by measuring the dissociation constant of human Interleukin-6 (IL-6) and anti-IL-6 interaction. Sandwich immunoassay was used to generate fluorescence signal proportional to antigen-antibody conjugate pairs. A portable CCD based spectrometer setup was used to record spectral profile of the fluorescence signal. The measured value of dissociation constant k(D) for IL-6 and capture anti-IL-6 (clone MQ2-13A5) antibodies at room temperature is588 ±19 pM .